SMART FARMING USING A SOLAR POWERED AQUAPONICS SYSTEM FOR A SUSTAINABLE FOOD PRODUCTION - Zainal Alam, Muhd Nazrul Hisham; Kamaruddin , Mohd Johari; Samsudin , Sani Amril; Othman, Raudhah; Mohammad Radzi , Nur Hanis; Emmanuel , Abioye Abiodun; Zainal Abidin , Mohamad Shukri (Malaysian Journal of Science, 2023)
This paper discusses the prospect of utilization of solar energy for aquaponics operation. Aquaponic is a platform for farmers to simultaneously grow fish and plants in a same unit. It is sustainable and produces little waste. The need of pumps for continuous water recirculation and air supply within the system could be a hindrance in the aquaponics operation especially if the unit is nowhere near any power outlet. It is indeed a visible solution as Malaysia located at equator and receives average sunlight 9 hours a day throughout the year with solar intensity as high as 1800-1900 kWh/m2. The work presents detail equipment for establishment of suitable solar PV system for aquaponics operation and reviews utilities of aquaponics platform that can be supported using solar energy. Possible integration of Internet-of-Things (IoT) for remote monitoring of such solar operated aquaponics unit is also discussed. Analysis showed that even when operated with full energy supply for only 12 hours, the yield and growth rates of the crop and fish grown in the system powered remains unaffected. This signified the potential for the use of solar energy as alternative energy for operation of the aquaponics unit. The main advantage perhaps is the realization of aquaponics setup in remote area where electricity is not accessible. Installation cost may be relatively high (100W PV system could cost nearly RM 600 for installation) but for a long run, it is highly beneficial as utility cost and cost for installing the national grid can be significantly reduced. Summarizing, the project introduced the concept of smart farming via aquaponics for a sustainable production of crop and fish using a renewable and clean solar energy for its operation.